Feasibility of Establishing and Re-operation of Industrial Projects in Iraq Through import-substitution strategy - Fadhel Kazem*, Durgham; Mahmoud Rashid Alani, Thaer (Journal of Economics and Administrative Sciences, 2024)
The research idea originated from the significance of the industrial sector and its pivotal role in inducing structural and systemic changes at the national economic level. Given the numerous challenges the industrial sector faces in Iraq, many industrial projects have partially or entirely ceased operations. In contrast, state-owned industrial companies have become a burden on the government. Import substitution through manufacturing is considered one of the leading strategies and most vital industrial approaches that have historically catalyzed industrial growth and structural transformations in the economy. This has been evident in the development of countries that initially relied on primitive economic models centred around simple agriculture and the export of raw materials and transitioned into diversified economies with a significant industrial component, producing numerous high-quality and technologically advanced products. Based on this, the study aims to assess the compatibility of this strategy with the current Iraqi economic landscape. It seeks to shed light on inactive industrial projects and companies, exploring the feasibility of reactivating them or establishing new industrial ventures. Priority will be given to projects aligned with its objectives and goals. Additionally, the study aims to provide a forward-looking perspective on the state of the industry in Iraq's prospects, diagnose existing problems, and attempt to find solutions and remedies that can contribute to establishing a reliable industrial sector.